Reinventing Privatization: A Political Economic Analysis of the Social Health Organizations in Brazil. (January 2021) - Turino, Fabiana; Filippon, Jonathan; Sodré, Francis; Siqueira, Carlos Eduardo
The Brazilian state apparatus was reformed throughout the 1990s, influenced by New Public Management (NPM). NPM was embodied in the health care sector by the creation of Social Health Organizations ( Organizações Sociais de Saúde or OSS), private non-profit entities to provide welfare services. We performed a systematic review of the literature outlining the origins and role of OSS in Brazil. Our selected articles (peer-reviewed) cover the origins/performance of OSS and their services provision between 1998 and 2018, in English or Portuguese. Databases used were Lilacs, Bireme, Medline, Pubmed, and SciELO. We identified 4, 732 articles applying a pre-defined set of descriptors, from which we selected 49 for analysis. The main findings reveal that NPM is the central theme of most articles about OSS in Brazil (n = 26). There is evidence corroborating our hypothesis that transferring management of public health care services to private non-profit organizations is a softer version of privatization as, although financing is kept public, the rationale and ethos of OSS services institutionally and operationally mimic the private sector. The practical consequence is that attainment of health care in Brazil ends up being neither fully commodified (based on ability to pay) nor fulfilled as a citizen's right following its national constitution.